Inventory Information System Audit Using Cobit 5 Domain MEA at PT. Telkom Akses Pontianak - Noor Hellyda Hermawati; Susy Rosyida (LPPM Universitas Bina Sarana Informatika, 2022)
PT. Telkom Akses Pontianak has an inventory system that has been used so far. During the research, several findings were found, such as information related to material availability, an ineffective system related to expenditure data that has an impact on the company's periodic reports, and the lack of optimization of existing human resources. so that the existing problems become the basis for conducting an audit of the information system used. The audit refers to the COBIT 5 framework using the MEA Domain. The results of the capability level of each MEA subdomain itself and the Gap Analysis are found. With the capability value of MEA 01 subdomain worth 3.83, MEA 02 subdomain worth 3.60, and MEA 03 subdomain worth 3.69, with an average value of 3.70 with Predictable Process description which means the object under study has reached the process. set runs within a defined limit to achieve the process objectives. And with the Gap Analysis calculation, namely the MEA 01 subdomain worth 1.2, MEA 02 subdomain worth 1.4, and MEA 03 subdomain worth 1.3, with an average value of 1.3 which means the company still needs to improve related to information systems. Inventory is used to obtain optimal results for all stakeholders.